INVESTMENT REGULATION BETWEEN BRAZIL AND ANGOLA: INTERNAL FACTORS, INTERNATIONAL CONTEXT AND THE DESIGN OF THE AGREEMENT FOR COOPERATION AND FACILITATION OF INVESTMENTS (ACFI) - Xavier Junior, Ely Caetano; Morosini, Fabio; Ratton Sanchez Badin, Michelle (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The goal of this article is to contextualize the regulation of investment in Angola and Brazil, contrasting their distinctive approaches during the 1990s and the beginning of the years 2000, and analyzing how their divergent approaches were reconciled with the signature of the ACFI, in the beginning of 2015.